Techniques for colonial growth and protoplast production in Humicola grisea var. thermoidea - J. M. B. MACEDO; J. L. AZEVEDO (Fungal Genetics Reports, 1991)
Humicola grisea is a thermophilic, cellulolytic fungus, with significant biotechnological potential for protein secretion. For convenient growth on solid medium, 70% reduction in colony diameter was achieved by the addition of 20 mM sodium citrate to modified Aspergillus complete medium (Pontecorvo et al. 1953, Adv. Genet. 5:141-238).